Institutional Entrepreneurship: An Introduction - Magnus Henrekson; Tino Sanandaji (Research Institute of Industrial Economics (IFN), 2010)
In this introductory chapter to a collective volume,* we build on Baumols (1990) framework to categorize, catalog, and classify the budding research field that explores the interplay between institutions and entrepreneurship. Institutions channel entrepreneurial supply into productive or unproductive activities, which likely accounts for a great deal of the disparate economic development of nations. Whats more, entrepreneurship is not only influenced by institutionsentrepreneurs often shape institutions themselves. Entrepreneurship abiding by existing institutions is occasionally disruptive enough to challenge the foundations of prevailing institutions. Entrepreneurs also have the opportunity to evade institutions, which tends to undermine the effectiveness of the institutions in question, or cause them to change for the better. Lastly, entrepreneurs can directly alter institutions through innovative political entrepreneurship. Similar to business entrepreneurship, innovative political activity can be either productive or unproductive, depending on the entrepreneurs incentives.
Keywords: H32; L50; M13; O31; P14; 330; Entrepreneurship; Innovation; Institutions; Property rights; Regulation; Self-employment; Entrepreneurship-Ansatz; Institutionelle Infrastruktur; Innovation; Immaterialgüterrechte; Regulierung; Selbstständige